Microstructure and reconstitution of freeze-dried gum Arabic at a range of concentrations and primary drying temperatures - Malik, N.; Muttakin, S.; Lopez-Quiroga, E.; Watson, N.J.; Fryer, P.J.; Bakalis, S.; Gouseti, O. (Elsevier, 2020)
Freeze-drying is an energy intensive unit operation used for the production of dehydrated foods, such as instant coffee and dried fruits, and results in high sensorial, nutritional and reconstitution properties of the final products. Understanding the relationships between operating conditions and product quality is essential to design processes that are energy efficient, whilst producing high quality dried foods. In this work, the properties (microstructure and reconstitution) of freeze-dried gum arabic samples (with initial concentrations ranging between 20 and 60% solids by weight) were evaluated. The materials were dried at three different primary drying shelf temperatures, Ts (- 20, - 30 and - 40 ◦C). Sample temperatures recorded throughout freeze-drying were close to the pre-set Ts, with the exception of the 60% initial concentration system, where the sample was hotter than the shelf by 10–15 ◦C, in particular on increasing Ts. This was attributed to a combination of local temperature and pressure conditions that may have resulted in partial melting of the material. For the 20–50% systems, the properties of the freeze-dried materials were mainly affected by the initial concentration of the system, with increasing initial concentration generally resulting in lower porosities (ranging between 20 and 40%) and higher reconstitution times (ranging between 0.5 and 10min for 95% reconstitution). Pores were generally needle-shaped and <200 μm. Large (200–1800 μm), circular pores were observed in high initial concentration systems, and they were dominant in the microstructure of the freeze-dried 60% sample. The presence of these large bubbles was linked to the partial melting of the material, which enabled its expansion and puffing. For the 60% system, primary drying temperature had a profound effect on the properties of the freeze-dried solid, with samples dried at higher temperature showing higher porosity (e.g. 60–70% for Ts = -¬¬ 20◦C) and faster reconstitution rates (e.g. 3min for 95% reconstitution at Ts = - 20◦C). Overall, this study demonstrates the significance of formulation and shelf temperature on the porous structure of freeze-dried samples, which directly influences product performance.